EVALUATION OF THE MECHANICAL PROPERTIES AND RESIDUAL MONOMER CONTENT OF COPOLYMER ACRYLIC RESINS POLYMERIZED BY DIFFERENT METHODS - Ayşegül Köroğlu; Onur Şahin; Doğu Ömür Dede; Şeyda Adıgüzel; Baki Hazer (Selcuk Dental Journal)
Background:The aim of this study was to evaluate the effect of adding four different monomers on the flexural strength, elastic modulus, impact strength and residual monomer content of denture base resins polymerized by copolymerization mechanism.Methods:Butyl methacrylate (BMA), Isobutyl mathacrylate (IBMA), 2-hydroxyethyl methacrylate (HEMA) and methacryl-polyhedral silsesquioxane (POSS-MA) were added to monomers of conventional heat (HP) and microwave polymerized (MP) polymethyl methacrylate (PMMA) resin at the concentrations of 2%, 5% and 10% per volume. The flexural strength, elastic modulus and impact strength of specimens were measured with an universal testing machine and Charpy-type impact tester. Residual monomer contents were determined by high performance liquid chromatography (HPLC) method. Results:10% IBMA and 10% HEMA enhanced the flexural strength of HP resin. For the elastic modulus of MP resin, significant differences observed between the control group and 2 and 5% IBMA, 5 and 10% HEMA, and 5% POSS-MA groups (P<.05). Copolymerization mechanism had no positive effect on the impact strength of denture base resins. Significant differences were observed between the residual monomer of control group and 10% IBMA, 10% BMA, 10% POSS-MA groups of HP resin (P<.05). In MP resin group significant differences were observed between control group and 5% IBMA, 2-5-10% HEMA groups (P<.05).Conclusions: Copolymerization process was effective on the flexural strength of HP denture base resin with 10% IBMA and 10 % HEMA. However the process caused an increase in the residual monomer content of some resin groups. Keywords: Denture base resin, copolymer, flexural strength, impact strength, residual monomer.